2022
DOI: 10.3389/fpubh.2022.942550
|View full text |Cite
|
Sign up to set email alerts
|

Desirable but not feasible: Measures and interventions to promote early childhood health and development in marginalized Roma communities in Slovakia

Abstract: Roma are the largest and most disadvantaged ethnic minority in Europe often facing generational poverty, and limited access to education, employment, housing, and various types of services. Despite many international and national initiatives, children from marginalized Roma communities face multiple risks and are being disadvantaged as early as from conception onward. We, therefore, aimed to identify measures and/or interventions targeting equity in early childhood health and development in marginalized Roma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Poverty and social exclusion are likely contributing significantly to experiencing stress in mothers and having adverse effects on parenting practices [39,40]; thus, supporting families in providing a nurturing environment for their children and providing opportunities to strengthen parenting skills might help to better the mental health of young children and influence their health outcomes later in life. Previous research has shown that addressing poverty in MRCs to support early childhood development is necessary but not easily implemented due to unfavourable public discourse and lack of political will [2]. These arguments can also be used in advocating for enhancement of living conditions in MRCs, focusing on sources of stress that stem from poverty.…”
Section: Implications For Practice Policy and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Poverty and social exclusion are likely contributing significantly to experiencing stress in mothers and having adverse effects on parenting practices [39,40]; thus, supporting families in providing a nurturing environment for their children and providing opportunities to strengthen parenting skills might help to better the mental health of young children and influence their health outcomes later in life. Previous research has shown that addressing poverty in MRCs to support early childhood development is necessary but not easily implemented due to unfavourable public discourse and lack of political will [2]. These arguments can also be used in advocating for enhancement of living conditions in MRCs, focusing on sources of stress that stem from poverty.…”
Section: Implications For Practice Policy and Future Researchmentioning
confidence: 99%
“…Although the Roma population in Slovakia is highly heterogeneous, approximately half of Roma live in more or less segregated localities referred to as marginalized Roma communities (MRCs) characterised by spatial and social distance from the majority population. People from MRCs often experience generational poverty, as well as limited access to education, employment, housing and various types of services, including healthcare [2], which causes material and financial hardship and leads to low quality of life [3,4]. Centuries of oppression and continuous discriminatory practices make social mobility and benefiting from social capital for people living in generational poverty in MRCs hardly reachable [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many of them suffer from economic and social deprivation compounded by anti-Gypsyism, prejudice and discrimination in spite of continued efforts to improve their situation. One of the features of deprivation has been that many Roma live in segregated colonies ( 2 , 3 ). Compared with the non-Roma population in Europe, Roma tend to be in less favorable health, reflected by lower life expectancy, higher infant mortality, and lower vaccination rates ( 4 ).…”
Section: Introductionmentioning
confidence: 99%